LINGUISTIC PERSONALITY IN ANTONYMS OF POEMS OF ENGLISH AND KARAKALPAK (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article is devoted to expressing of oppositeness of meaning or antonyms in diverse poems of English and Karakalpak which describe the poets’ opinion, idea and feeling but also state. The author indicates that Lyons’s classification for oppositeness of meaning is very remarkable for understanding of the message of the poems.